Dairy Farmers Attitude And Preferences Towards Contract Dairy Farming System - Kolekar, D. V.; Meena, H. R.; Bangar, Y. C. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present study was conducted purposively in Satara district of Maharashtra to ascertain attitude and preferences towards contract dairy farming by using instrument consisting of 7 point Likert scale. The study reveals that majority of dairy farmers prefers contracts with no restrictions regarding volume control and shows the willingness for arrangements with a long duration. Also dairy farmers are rather averse to risk-taking and believe that close contractual relationships could also be beneficial for them. While dairy farmers have positive preferences towards the contract attributes pricing, volume regulation, duration and intensity of the settlement.